2011
DOI: 10.1074/jbc.m110.212597
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-type Protein Tyrosine Phosphatase β (RPTP-β) Directly Dephosphorylates and Regulates Hepatocyte Growth Factor Receptor (HGFR/Met) Function

Abstract: Protein tyrosine phosphorylation is a ubiquitous, fundamental biochemical mechanism that regulates essential eukaryotic cellular functions. The level of tyrosine phosphorylation of specific proteins is finely tuned by the dynamic balance between protein tyrosine kinase and protein tyrosine phosphatase activities. Hepatocyte growth factor receptor (also known as Met), a receptor protein tyrosine kinase, is a major regulator of proliferation, migration, and survival for many epithelial cell types. We report here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 58 publications
(29 reference statements)
0
13
0
Order By: Relevance
“…FeNTA-induced tumours demonstrated a 16–500-fold increase in the expression of receptor-type tyrosine-protein phosphatase-ζ (RPTPζ; also known as PTPRZ1). RPTPζ participates in multiple signalling pathways 146,147 . The authors observed that, concomitantly with RPTPζ overexpression, nuclear β-catenin expression was increased, with significant activation of the β-catenin target genes cyclin D1 ( Ccnd1 ), Jun , Myc , fos-like antigen 1 ( Fosl1 ; also known as Fra1 ) and Cd44 .…”
Section: Iron Affects Wnt Signallingmentioning
confidence: 99%
“…FeNTA-induced tumours demonstrated a 16–500-fold increase in the expression of receptor-type tyrosine-protein phosphatase-ζ (RPTPζ; also known as PTPRZ1). RPTPζ participates in multiple signalling pathways 146,147 . The authors observed that, concomitantly with RPTPζ overexpression, nuclear β-catenin expression was increased, with significant activation of the β-catenin target genes cyclin D1 ( Ccnd1 ), Jun , Myc , fos-like antigen 1 ( Fosl1 ; also known as Fra1 ) and Cd44 .…”
Section: Iron Affects Wnt Signallingmentioning
confidence: 99%
“…PTKs transmit extracellular signals and regulate various cellular process which are initiated through dimerization, induced by ligand‐binding, leading to autophosphorylation [89,90]. RPTPs can act as negative regulators of PTK signaling: for example, RPTPO ( RPTPO ) can diminish neurotrophin‐3‐induced TrkC phosphorylation [91], RPTPζ exerts an influence on TrkA [92,93], and RPTPβ ( PTPRB ) dephosphorylates its substrate Met, specifically at the binding site for several downstream effector molecules [94].…”
Section: Protein Tyrosine Kinases Substrates or Ligands Of Rptps?mentioning
confidence: 99%
“…Western blot was performed as previously described (Bank et al 1997; Xu et al 2011). Primary antibodies were incubated with PVDF membrane for one hour at room temperature, and immunoreactive protein bands were imaged and quantified by enhanced chemifluorescence, using a STORM Molecular Imager, with ImageQuant software (GE HealthCare, Piscataway, NJ).…”
Section: Methodsmentioning
confidence: 99%